2006
DOI: 10.1016/j.ejvs.2005.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair for Aorto-enteric Fistula: A Bridge Too Far or a Bridge to Surgery?

Abstract: Endovascular sealing of AEF is a promising technique, which provides time to treat shock, local and systemic infection, and co-morbidity. This creates a better situation to perform open repair in the future with possibly better outcome. Danger of reinfection remains high. Endovascular sealing of AEF should, therefore, be seen as a bridge to open surgery when possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 17 publications
1
63
0
4
Order By: Relevance
“…Within 12 months, over half of the patients who survived the initial surgery showed signs of reinfection and required reoperation despite ongoing antibiotic treatment [ 33 ]. These results reinforce the principle that endovascular therapy for AEF should be viewed as a temporizing measure to stop exsanguination and allow preparation for defi nitive graft excision.…”
Section: Discussionsupporting
confidence: 60%
“…Within 12 months, over half of the patients who survived the initial surgery showed signs of reinfection and required reoperation despite ongoing antibiotic treatment [ 33 ]. These results reinforce the principle that endovascular therapy for AEF should be viewed as a temporizing measure to stop exsanguination and allow preparation for defi nitive graft excision.…”
Section: Discussionsupporting
confidence: 60%
“…Artificial graft infections, which are mainly associated with polyester grafts, often lead to fatal complications such as the formation of an aortoenteric fistula or pseudoaneurysm. [17][18][19][20] To manage these complications, homograft replacement with an omentum flap can be applied; however, despite a great amount of effort being expended, the outcomes are often not satisfactory. 17 In addition, the number of potential homografts is limited, and suitable replacements are not always available from tissue banks.…”
Section: Discussionmentioning
confidence: 99%
“…The palliative covering of fistulas with ready-made endovascular stent grafts has also been reported although the frequency of recurrent infections among such cases is extremely high. 17,18 Thus, the Bio stent graft, which is covered by connective tissue, may be useful for the primary management of graft infections or aortoenteric fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of percutaneous endovascular techniques revolutionized the management of AEF, especially for patients unsuitable for open surgery. Danneels et al(2006) reviewed 15 cases between 1999 and 2005 and concluded that endovascular sealing of AEF provides time to treat shock, local and systemic infection, and comorbidity, which creates a better situation to perform future open repair, with possibly better outcome.…”
Section: Discussionmentioning
confidence: 99%